Facilitando, treinando e premiando a Olimpíada de Física na região de São José do Rio Preto-SP - Farineli, Lindomar da Costa Lima [UNESP]; Oliveira, Leandro Cristante de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The "Athletes of physics" is a project focused on the integration of University and society started during the year of 2014 with the purpose of spread, promote and provide support to students to attend the Brazilian Physics Olympiad sponsored by the Brazilian Physics Society at São José do Rio Preto – SP region. This University Extension proposal was planned after the evaluation of the School Census results of 2013 to São José do Rio Preto region, which indicates that 80.6% of elementary school science teachers have a physics degree and that only 18.1% of teachers of secondary school who teach physics have the licenciature (a kind of teaching permission) degree in Physics. Still, it must be emphasized the low demand by physics courses in the role country and the vacancies for physicists. The previous results of OBF indicate a small number of medalists although the great potential of the region. In this work, it will present initiatives and current actions to promote the areas of physics and related fields at São José do Rio

O projeto de extensão universitária “Atletas da Física” iniciou suas atividades no ano de 2014. Seu objetivo é divulgar, promover e auxiliar na realização da Olimpíada Brasileira de Física promovida pela Sociedade Brasileira de Física na Região de São José do Rio Preto – SP. A proposta foi motivada pela avaliação dos dados do Censo Escolar de 2013 da região de São José do Rio Preto, que indicam que 80,6% dos professores de ciências do ensino fundamental possuem licenciatura e que no ensino médio apenas 18,1% dos professores que lecionam Física possuem licenciatura em Física. Ainda, devem ser ressaltadas as baixas procuras nos cursos superiores de Física e a falta desses profissionais no mercado. Os resultados das edições anteriores da OBF indicam um baixo número de medalhistas, apesar do grande potencial da região. Neste trabalho, serão apresentadas iniciativas e ações em andamento para a promoção da Física e de áreas afins na região de São José do Rio Preto-SP desenvolvidas pelo projeto de extensão universitária mencionado.
Keywords: Brazilian Physics Olympiad; Promotion of Physics field; Scientific dissemination; Olimpíada Brasileira de Física; Promoção da área de Física; Divulgação científica